Cancel cancer: The immunotherapeutic potential of CD200/CD200R blockade - Choe, Deborah; Choi, Dongwon (Frontiers in Oncology, 2023)
Immune checkpoint molecules function to inhibit and regulate immune response pathways to prevent hyperactive immune activity from damaging healthy tissues. In cancer patients, targeting these key molecules may serve as a valuable therapeutic mechanism to bolster immune function and restore the body’s natural defenses against tumors. CD200, an immune checkpoint molecule, is a surface glycoprotein that is widely but not ubiquitously expressed throughout the body. By interacting with its inhibitory receptor CD200R, CD200 suppresses immune cell activity within the tumor microenvironment, creating conditions that foster tumor growth. Targeting the CD200/CD200R pathway, either through the use of monoclonal antibodies or peptide inhibitors, has shown to be effective in boosting anti-tumor immune activity. This review will explore CD200 and the protein’s expression and role within the tumor microenvironment, blood endothelial cells, and lymph nodes. This paper will also discuss the advantages and challenges of current strategies used to target CD200 and briefly summarize relevant preclinical/clinical studies investigating the immunotherapeutic efficacy of CD200/CD200R blockade.